Use of Angiotensin-converting Enzyme Inhibitor Therapy and Dose-related Outcomes in Older Adults with New Heart Failure in the Community - Rochon, Paula A (Blackwell Science Inc, 2004)
OBJECTIVE: To evaluate the dose-related benefit of angiotensinconverting enzyme (ACE) inhibitor therapy among older adults with heart failure and to evaluate whether low-dose ACE inhibitor therapy is better than none. DESIGN: Observational cohort study. SETTING: Community-dwelling older adults in Ontario, Canada. PATIENTS/PARTICIPANTS: We identified 16,539 adults 66 years or older who survived 45 days following their first heart failure hospitalization discharge. MEASUREMENT AND MAIN RESULTS: Multivariate techniques including propensity scores were used to study the association between the dose of ACE inhibitor therapy dispensed and 3 outcomes: survival, survival or heart failure rehospitalization, and survival or all-cause hospitalization at 1 year of follow-up. Logistic regression models explored the association between initial dose dispensed and subsequent dose reduction or drug cess-ation. Overall, 10,793 (65.3%) of patients were dispensed ACE inhibitor therapy, with more than a third (3,935; 36.5%) initiated on low-dose therapy. Relative to dispensing of lowdose ACE inhibitor therapy, nonuse was associated with increased mortality (hazard ratio [HR], 1.12; 95% confidence interval [CI], 1.02 to 1.22). Dispensing medium-dose therapy provided a benefit similar to low-dose (HR, 0.94; CI, 0.86 to 1.03) and dispensing of high-dose therapy was associated with improved survival benefit (HR, 0.76; CI, 0.68 to 0.85). Relative to dispensing of low-dose ACE inhibitor therapy, dispensing high-dose conferred a benefit (HR, 0.87; CI, 0.80 to 0.95) on the composite outcome of 1-year mortality or heart failure hospitalization and the composite outcome of 1-year mortality or all-cause hospitalization (HR, 0.87; CI, 0.81 to 0.93). Relative to those dispensed low-dose ACE inhibitor therapy, those initially dispensed high-dose therapy were twice as likely to have their subsequent dose reduced or the therapy discontinued (odds ratio, 2.36; CI, 2.07 to 2.69). CONCLUSION: Our findings suggest that when possible, older adults should be titrated to the higher doses of ACE inhibitor therapy evaluated in clinical trials. If older adults cannot tolerate higher doses, then low-dose ACE inhibitor therapy is superior to none. High-dose ACE inhibitor therapy is not as well tolerated as lower doses.